2013
DOI: 10.1684/epd.2013.0560
|View full text |Cite
|
Sign up to set email alerts
|

SISCOM and FDG‐PET in patients with non‐lesional extratemporal epilepsy: correlation with intracranial EEG, histology, and seizure outcome

Abstract: Aims. To assess the practical localising value of subtraction ictal single‐photon emission computed tomography (SISCOM) coregistered with MRI and 18F‐fluorodeoxyglucose positron emission tomography (FDG‐PET) in patients with extratemporal epilepsy and normal MRI. Methods. We retrospectively studied a group of 14 patients who received surgery due to intractable epilepsy and who were shown to have focal cortical dysplasia, undetected by MRI, based on histological investigation. We coregistered preoperative SISCO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 34 publications
1
21
0
4
Order By: Relevance
“…Depending on their origin of onset among other factors, seizures may have different propagation patterns that can influence SISCOM outcome. A possible explanation is that frontal and parietal seizures may propagate faster and more easily to large areas of the brain, resulting in poorer SPECT localizations …”
Section: Discussionmentioning
confidence: 99%
“…Depending on their origin of onset among other factors, seizures may have different propagation patterns that can influence SISCOM outcome. A possible explanation is that frontal and parietal seizures may propagate faster and more easily to large areas of the brain, resulting in poorer SPECT localizations …”
Section: Discussionmentioning
confidence: 99%
“…Twenty of 23 patients were seizure-free at 4 years after a limited areas resection that showed a Taylor-type focal cortical dysplasia in all cases. Another study on 14 patients with similar clinical characteristics has shown that the complete resection of the dysplastic cortex localized by FDG-PET, SISCOM, or intracranial EEG is a reliable predictor of favorable post-operative outcome (194). Therefore, in extra-temporal lobe epilepsies, PET is best used as a guide for focusing the review of MRI in the search for subtle overlooked cortical dysplasia or to inform the placement of intracranial electrodes.…”
Section: Positron Emission Tomographymentioning
confidence: 99%
“…Nevertheless, a later study has shown an equivalent or even better yield for extra-temporal epilepsy [86% in extra-temporal compared to 67% in temporal lobe epilepsy (207)]. Some studies that included specifically patients with non-lesional extra-temporal epilepsy have shown that the resection of the SISCOM area is related to good post-operative outcome (194, 208). Similar findings have been corroborated by a prospective study (209), which has shown that if SISCOM is concordant with the future resection site, there are higher chances of having good to excellent post-operative outcome.…”
Section: Single Photon Emission Computed Tomographymentioning
confidence: 99%
“…However, the effectiveness of 3 T relative to 1.5 T MRI on improving surgical outcome remains to be assessed. In patients with nonlesional focal epilepsy, additional noninvasive diagnostic tests such as MEG, FDG‐PET, or SPECT can assist in the presurgical localization of the epileptogenic zone . The few studies that have assessed the diagnostic performance of combined functional imaging and its role on surgical decision making were conducted primarily in adults .…”
mentioning
confidence: 99%